Consumer Buying Behavior toward Online Shopping: A Case of Daraz in Kathmandu Valley - Karki, Raisa (Nepalese Journal of Economics, 2025)
This study examines consumer buying behavior toward online shopping of Daraz in Kathmandu Valley. Thw dependent variable is consumer buying behavior. The independent variables are advertisement, price, return policy, product risk, and trust on online shopping. The study is based on primary data with 142 observations. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of different factors influencing consumer buying behavior toward online shopping (Daraz) in Kathmandu valley. The study shows that advertisement is positively correlated to consumer buying behavior. It means that increase in advertisement in Daraz leads to increase the consumer buying behavior in people. Similarly, there is a positive relationship between price and consumer buying behavior. It means that better the price, lead to positivity in consumer buying behavior. Furthermore, there is a positive relationship between return policy and consumer buying behavior. It indicates that increase in return policy leads to increase the efficiency of consumer buying behavior. In contrast product risk has a positive relationship with consumer buying behavior. It means that less product risk, leads to increase the consumer buying behavior. Similarly, there is a positive relationship between trust on online shopping and consumer buying behavior. It indicates that increase in trust leads to increase the efficiency of consumer buying behavior.